1938
DOI: 10.1037/h0058033
|View full text |Cite
|
Sign up to set email alerts
|

Motivation in learning. VIII. Equivalent amounts of electric shock for right and wrong responses in a visual discrimination habit.

Abstract: The first study of this series demonstrated that when shock is given for correct responses learning is accelerated as if it were given for wrong responses. It was concluded that the function of shock after the point of choice is "to make the animal respond more readily to the significant cues in the learning situation." (l,p.276) In this first experiment a rat of the shock-wrong group received about one-fifth of the amount of shock received by a rat in the shock-right group. And yet, the acceleration produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
1

Year Published

1948
1948
1982
1982

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 5 publications
3
29
1
Order By: Relevance
“…The point to be emphasized is that in terms of all measurestrials, errors, reinforcements-the differences between our shock-right group and no-shock group are not statistically significant although the differences between each of these groups on the one hand and the shock-wrong group on the other are statistically significant. These results are to be contrasted with those reported by Muenzinger et al (2) which show a significant difference between the shock-right and no-shock groups in favor of the former.…”
Section: University Of Missouricontrasting
confidence: 97%
“…The point to be emphasized is that in terms of all measurestrials, errors, reinforcements-the differences between our shock-right group and no-shock group are not statistically significant although the differences between each of these groups on the one hand and the shock-wrong group on the other are statistically significant. These results are to be contrasted with those reported by Muenzinger et al (2) which show a significant difference between the shock-right and no-shock groups in favor of the former.…”
Section: University Of Missouricontrasting
confidence: 97%
“…Similar paradoxical findings were also revealed in a series of discrimination learning experiments with white rats by Muenzinger and his students (21,23). In their experiments" it appeared that punishment tended to fixate responses instead of inhibiting them " (17, p.424)***.…”
mentioning
confidence: 63%
“…The paradoxical finding reported by Muenzinger and his colleagues (e. g., Muenzinger, 1934;Muenzinger et al, 1938) that shock for the correct response facilitates discrimination performance appears generally accepted despite the results of more recent investigations which have failed to demonstrate the effect and point up the import of considering various classes of determining variables, including training procedures and shock parameters. In one of these studies (Wischner et al, 1963), investigation of the effect of shock intensity showed that, with a non-correction procedure, increasing intensities of shock reduced errors for shock-wrong (SW) groups but increased them for shock-right (SR) groups, all of the latter being inferior to no-shock (NS) controls.…”
Section: Problemmentioning
confidence: 70%